Frequency reconfigurable substrate integrated waveguide (SIW) cavity F-shaped slot antenna - Najib Mohammed Ahmed AL-Fadhali; Huda Abdul Majidd; Rosli Omar; Mohd Hezri Mokhtar; Najmaddin Abo Mosali (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
This paper shows a frequency reconfigurable SIW F-slot suitable for some applications. Configurability is accomplished by embeddings PIN diode switches in the 'F' slot. The proposed antenna is equipped for exchanging between working band of 3.172 GHz to 3.606 GHz in four different narrow bands and it underpins the cognitive system for LTE2300, WiMAX and WLAN. For each case reflection coefficient is ascertained, it keeps up less than -10 dB all through the resonating frequency in all instances of diode switching. The electromagnetic energy is kept inside the cavity because of the frame of a metallic vias. In all instances of diodes exchanging, it's uncovered a decent effectiveness of efficiency and gain.